ASTHENOSPHERE AND PLATES OF NORTHEAST ASIA - Khanchuk A.I.; Petrishchevskii A.M. (My University, 2007)
In the territory of Northeast Asia north of latitude 56, the three largest lithospheric plates (Eurasian, North American, and Pacific) and some plates of second rank (Amur, Sea of Okhotsk, and Sea of Bering) are conjugated and their space–time interrelations are the subject of heated discussions. Tectonists diagnose boundaries and kinematic characteristics of plates proceeding from analysis of the tectonostratigraphic, paleogeographic, magmatic, and structural attributes observed in a thin superficial layer of the crust. Works of seismologists are based on the spatial distribution of centers of earthquakes and calculations of vectors of seismotectonic pressures in fields of strong seismic events. These systems of estimations do not always coincide during the characterization of spatial parameters and evolution of the lithospheric plates. In particular, the site of the modern boundary between the Eurasian (EAP) and North American (NAP) plates varies by more than 700 km in different estimations.